2017
DOI: 10.1002/alr.21979
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of nasal cytology and clinical factors in nasal polyps development in patients at risk: can the beginning predict the end?

Abstract: Our data suggest that early identification of inflammatory patterns and associated clinical factors in patients affected by chronic nonallergic sinonasal inflammation have a prognostic value that can help to identify patients with different risks of NP development. Our data confirm that detection of nasal eosinophilic inflammation represents an early marker for identification of a more aggressive inflammatory phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 38 publications
2
33
0
1
Order By: Relevance
“…In the present study, we evaluated the signi cance of clinical characteristics to differentiate between ECRSwNP and nonECRSwNP. In accordance with ndings from other studies [32][33][34], our study also showed signi cant differences between the two subphenotypes, with respect to symptom scores, E/M ratio, endoscopy scores and blood eosinophils.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we evaluated the signi cance of clinical characteristics to differentiate between ECRSwNP and nonECRSwNP. In accordance with ndings from other studies [32][33][34], our study also showed signi cant differences between the two subphenotypes, with respect to symptom scores, E/M ratio, endoscopy scores and blood eosinophils.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we evaluated the signi cance of clinical characteristics to differentiate between ECRSwNP and nonECRSwNP. In accordance with ndings from other studies [34][35][36], our study also showed signi cant differences between the two subphenotypes, with respect to symptom scores, E/M ratio, endoscopy scores and blood eosinophils.…”
Section: Discussionsupporting
confidence: 92%
“…AR, in fact, is typically characterized by a Th2 immune response involving IL-4, IL-5, and IL-13 which drives IgE production and recruitment of eosinophil granulocytes. It has been suggested [38][39][40][41][42] that eosinophils, by generating potent toxic agents (cationic proteins, oxygen-free radicals, and proinflammatory cytokines), may play a major role in initiating and perpetuating inflammation of sinonasal mucosa in patients with AR.…”
Section: Allergy and Chronic Rhinosinusitis (Crs) In Childrenmentioning
confidence: 99%